Inquérito sorológico para toxoplasmose em equinos na região de Botucatu-SP - Camossi, L. G. [UNESP]; Silva, A. V. [UNESP]; Langoni, Hélio [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2010)
The frequency of anti-T.gondii IgG antibodies was evaluated and compared in 253 sera samples of equines by modified agglutination test (MAT) and indirect immunofluorescent antibody test (IFAT). Fifteen samples (5.9%) were positive by IFAT and 32 (12.6%) by MAT. Significant difference between the two methods was found when a cutoff titer of 16 was established. There was no correlation with breed, gender, and age of horses examined.
Serological survey of toxoplasmosis in horses from Botucatu region, SP